WHY DID TADEUSZ RÓŻEWICZ TRANSLATE DRAGUTIN TADIJANOVIĆ’S “RING”? (ABOUT THE AUTHOR OF “NIEPOKÓJ” AS A TRANSLATOR OF SERBIAN AND CROATIAN POETRY) - Stankowska, Agata (Porównania, 2019)
The question asked in the title of the paper may be considered as clearly probabilistic and leading only to trivial answers such as: because he was aware of the importance of the work of the author of “Ring” for the Croatian lyric poetry; because in 1958 he took part in the 3rd Yugoslavian Festival of Poetry in Rijeka and, probably, met the Croatian poet there; because that particular poem seemed to him especially beautiful and important. This matter, today unsolved – since both of the poets are deceased – may be, however, a rhetorical introduction to the attempt to read Tadijanović’s poem as not-his-own, in fact, yet included as a quotation, part of contemplations made by Różewicz on the human condition in the 20th century. It is appropriate therefore to consider whether Tadijanović’s vision included in “Ring” reflects to certain extent the way in which Różewicz grappled with the experience of co-participation in death and historical catastrophe. That is the lead I try to follow in the paper. Hence I look at the way in which Różewicz places Tadijanović in his own poetical diction. I ponder how this poem can be illuminated with original texts written by Różewicz. Finally, I consider whether the translatological decision of the author of “Anxiety” is in any way connected with his fascination with the classical lyric poetry of Leopold Staff.